Effect of combination of behavioural intervention and nutrition education with brown rice (combine-brown) weight loss program on body composition and oxidative stress and among overweight and obese adults - Gee, Ong Mei (2023)
Brown rice is well known for its nutritious value. However, little is known regarding the effectiveness of a combination of behavioural intervention and nutrition education with brown rice (COMBINE-BROWN) weight loss program. The present study was divided into three phases. Phase I and II of the study's objectives were to determine the nutrition composition, textural, elemental and ultrastructure difference, and glycaemic response for the brown rice variety 1 and 2 (BR1 and BR2) and white rice variety (WR). Meanwhile, Phase III of the study mainly aimed to evaluate the difference in body composition, oxidative stress biomarkers among the control group (COMBINE Group) and intervention group (COMBINE-BR Group) in a 12 week intverention and subsequent 12 week follow-up. A total of 66 overweight and obese participants were allocated into two arms (COMBINE Group and COMBINE-BR Group) in a quasi-experimental design. In the intervention phase, 22 participants (33.33%) in the COMBINE Group and 7 (10.61%) participants in the COMBINE-BR Group dropped out from the study. Meanwhile, 37 participants in the COMBINE Group and 38 participants in the COMBINE-BR Group completed the follow-up at week-24. The body composition, body anthropometric, total scores of the impact of weight on quality of life-LITE, and total scores of physical activities using International Physical Activity Questionnaires were measured at 0-week, 12-week and 24-week. Meanwhile, the biochemical profiles, including glucose, lipid, and antioxidants, were determined at 0-week and 12-week. The final outcomes were measured using repeated measure ANOVA for time effect and time-treatment effect using both per-protocol (PP) and intention-to-treat (ITT) analyses as suggested by Consolidated Standards of Reporting Trials reporting guidelines. The finding from Phase I reported a greater nutritional composition and elements content in brown rice than in white rice. Meanwhile, in Phase II, an intermediate glycaemic index was reported for the rice varieties. In Phase III, both groups showed significant improvement (p<0.05) in weight loss, total body fat percentage, lipid profile, antioxidants level (GPX and GR), total physical activity and the scores of IWQOLLITE in the 12-week intervention period. The COMBINE-BR Group significantly reduced oxidative stress compared to the COMBINE Group, as shown by a significant reduction of TBARS biomarkers. In parallel with PP analysis, the results showed a significant difference (p<0.001) in mean weight, body fat percentage, and oxidative stress biomarkers for both groups using ITT analysis based on time. Meanwhile, significant time-treatment interaction (p<0.05) was observed for weight and oxidative stress biomarkers (TBARS). Based on the final outcomes of intention-to-treat analyses, although the COMBINE Group showed more significant weight loss (- 6.88kg) than the COMBINE-BR Group (-4.34 kg) in the intervention phase, the COMBINE-BR Group showed a weight maintenance trend (-0.37 kg) as compared with the COMBINE Group (increased by 1.75 kg) during follow-up evaluation at week-24. In conclusion, adequate intake of white rice, physical activity and behavioural modification in a consistent mode might aid weight loss. Meanwhile, brown rice could be beneficial in adding extra minerals, dietary fibre and antioxidant properties, which might act as an alternative therapeutic regimen for weight maintenance, improve the immune system and thus prevent obesity-related diseases.